Korelasi Kadar Trombosit dengan parameter NS1Ag Pada Pasien Demam Berdarah: Studi Literatur Review - Liany, Ayundah Novie; Lidyaningrum, Galuh Ajeng; Oktaruliawan, Veronika; Saputra, Eduwardo Roy; Nugroho, Rhenald Aditya; Wahyudi, Eko Bambang; Setyaputri, Nabila Hani; Putri, Wafiq Zahro; Anggraeni, Rifka Wahyu; Alhafiz, Rafaiz Filaili; Rini, Chylen Setiyo (Institut Teknologi Kesehatan dan Sains Wiyata Husada Samarinda, 2025)
Dengue Fever (DHF) is a disease caused by infection with the Dengue virus, from the family Flaviridae and genus Flavivirus. Dengue virus consists of 4 serotypes. The virus is transmitted to humans through the bite of infected mosquitoes, especially Aedes Aegypti mosquitoes. In detecting dengue virus infection, laboratory examinations can be carried out such as platelet count, NS1Ag and dengue IgG IgM. The method used is a literature study by finding references from relevant journals. The results showed that there was a significant correlation between platelet levels and NS1Ag parameters in dengue hemorrhagic fever patients. And there is no relationship between clinical symptoms and NS1Ag parameters in dengue hemorrhagic fever patients. fever patients.